Transdermal drug delivery and patches—An overview. Issue 6 (8th April 2020) - Bird, David; Ravindra, Nuggehalli M.
Abstract: Transdermal drug delivery is a multibillion‐dollar industry, with an average of one transdermal being approved by the Federal Drug Administration every 2.2 years. The first transdermal drug patch was approved by the Food and Drug Administration approximately 40 years ago, meriting a systematic review of the technology, industry and products. Patches are a unique technique offering the ability for transdermal drug delivery systems on demand. The limiting factors for transdermal delivery systems are the physicochemical and pharmacokinetic properties of an active drug enabling delivery across the skin. An overview of the skin anatomy and natural barrier it presents for pharmaceuticals to be administered transdermally is presented in this study. The clinical trials, patents, commercialization, advantages and limitations of the technology are examined. Finally, 3D printing technologies are discussed, emphasizing the tailorable transdermal system, enhancing bioavailability and revolutionizing current 'one size fits all' manufacturing approach with capabilities that are utilized throughout the drug development timeline.